2017
DOI: 10.1186/s13104-017-2725-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and drug susceptibility pattern of group B Streptococci (GBS) among pregnant women attending antenatal care (ANC) in Nekemte Referral Hospital (NRH), Nekemte, Ethiopia

Abstract: ObjectiveThe main objective of this study was to determine the prevalence and drug susceptibility pattern of group B Streptococci (GBS) among pregnant women. The specific objectives include; (1) To determine the prevalence of GBS colonization among pregnant women (2) To determine the drug susceptibility pattern of GBS among pregnant women and (3) To identify associated risk factors with GBS colonization among pregnant women.ResultsThe median age of the participants was 24.5 years (range 16–38) and 86% particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
25
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 24 publications
23
25
2
1
Order By: Relevance
“…Previous studies have reported GBS to be evenly susceptible to penicillin, ampicillin and cephalosporins (18,22) even though bacteria with increasing minimum inhibitory concentration to penicillin and ampicillin have been reported (18,22). The high resistance of GBS to penicillin G reported in our study mirrors that reported by Mengist, Zewdie (23) of 77.3% (23). Findings of the current study partly agrees with those of Lu, Li (20), Yoon, Jo (24) and…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported GBS to be evenly susceptible to penicillin, ampicillin and cephalosporins (18,22) even though bacteria with increasing minimum inhibitory concentration to penicillin and ampicillin have been reported (18,22). The high resistance of GBS to penicillin G reported in our study mirrors that reported by Mengist, Zewdie (23) of 77.3% (23). Findings of the current study partly agrees with those of Lu, Li (20), Yoon, Jo (24) and…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported GBS to be evenly susceptible to penicillin, ampicillin and cephalosporins (17,21) even though bacteria with increasing minimum inhibitory concentration to penicillin and ampicillin have been reported (17,21). The high resistance of GBS to penicillin G reported in our study mirrors that reported by Mengist, Zewdie (22) of 77.3% (22). Findings of the current study partly agrees with those of Lu, Li (19), Yoon, Jo (23) andMengist, Zewdie (22) who reported a resistance to clindamycin of 55.7%, 55.4% and 50% respectively (19,22,23).…”
Section: Discussionsupporting
confidence: 91%
“…The high resistance of GBS to penicillin G reported in our study mirrors that reported by Mengist, Zewdie (22) of 77.3% (22). Findings of the current study partly agrees with those of Lu, Li (19), Yoon, Jo (23) andMengist, Zewdie (22) who reported a resistance to clindamycin of 55.7%, 55.4% and 50% respectively (19,22,23). However, the resistance in the three studies is higher than that reported in the current study of 30.4%.…”
Section: Discussionsupporting
confidence: 91%
“…Primary studies conducted in the East African countries showed the colonization rates ranged from 3.0% to 28.8% [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; Central Africa,20.0% [27,28]; Western Africa, 2.5% to 34.2% [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]; Southern Africa, 1.77% to 48.23% [49][50][51][52][53][54][55][56][57]…”
Section: Introductionmentioning
confidence: 99%